2018
DOI: 10.1038/s41598-018-25626-y
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus 2/9 delivery of Cre recombinase in mouse primary afferents

Abstract: Genetically-modified animal models have significantly increased our understanding of the complex central nervous system circuits. Among these models, inducible transgenic mice whose specific gene expression can be modulated through a Cre recombinase/LoxP system are useful to study the role of specific peptides and proteins in a given population of cells. In the present study, we describe an efficient approach to selectively deliver a Cre-GFP to dorsal root ganglia (DRG) neurons. First, mice of different ages w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…In this model, the Cre-driven removal of the translational STOP cassette makes it possible to rescue the expression of DOPr in a tissue-and/or cell-specific manner. We have previously demonstrated that the recombinant adenoassociated virus rAAV2/9-CBA-Cre-GFP predominantly targeted dorsal root ganglia (DRGs) following intrathecal administration (16). Interestingly, when administered to KO mice, our results showed that the antihyperalgesic effects of DLT II were partially reinstated 6 wk after the viral infection, supporting a role for DOPr expressed in primary afferents in the control of pain induced by a thermal stimulus (Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In this model, the Cre-driven removal of the translational STOP cassette makes it possible to rescue the expression of DOPr in a tissue-and/or cell-specific manner. We have previously demonstrated that the recombinant adenoassociated virus rAAV2/9-CBA-Cre-GFP predominantly targeted dorsal root ganglia (DRGs) following intrathecal administration (16). Interestingly, when administered to KO mice, our results showed that the antihyperalgesic effects of DLT II were partially reinstated 6 wk after the viral infection, supporting a role for DOPr expressed in primary afferents in the control of pain induced by a thermal stimulus (Fig.…”
Section: Resultssupporting
confidence: 58%
“…In addition, our mice models are different from the recently reported HA-DOPr KI mouse (48), since it can be used to produce conditional KI within specific targeted regions using a tissue-specific Cre recombinase mouse line or viral approaches. This possibility was investigated by the injection of the recombinant adenoassociated virus rAAV2/9-CBA-Cre-GFP, which preferentially targets lumbar DRGs when injected intrathecally (16). In a CFA-induced chronic pain model, we observed that the antihyperalgesic effect of DLT II (specific DOPr agonist) was partially reinstated in KO mice intrathecally injected with the virus, thereby supporting a reexpression of DOPr in the spinal cord, presumably on central terminals of primary afferents.…”
Section: Discussionmentioning
confidence: 82%
“…However, delivering genes by AAV injection into a peripheral organ to DRG neurons is challenging because of the low transduction capability of AAVs and the large anatomic distances involved in the PNS . A variety of AAV serotypes have shown little efficacy in transducing DRG neurons when injected subcutaneously, intramuscularly, or in an intraplantar manner in adult mice . To date, direct injection into DRG or intrathecal injection are the best ways of transducing DRG neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Mice showing less than 20% infected neurons were excluded from the analysis. A detailed characterization of rate of neuron transduction and neuron-specificity for both AAV (1/2) and AAV (9/2) in mouse DRG has been previously described 32 , 86 .…”
Section: Methodsmentioning
confidence: 99%